Cervical spine trauma: impact of different imaging classification systems in the clinical decision-making - Pagliei, Valeria; Bruno, Federico; Battista, Giuseppe; Iacopino, Antonio; Riva, Camilla; Arrigoni, Francesco; Palumbo, Pierpaolo; Bardi, Luca; Carbone, Mattia; Di Cesare, Ernesto; Masciocchi, Carlo; Splendiani, Alessandra; et al. (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Considering the high rate of mortality and permanent disability related to vertebral traumas, an early and detailed diagnosis of the trauma and subsequently an immediate and effective intervention are crucial. Cervical vertebral injury classifications guide treatment choice through a severity grade based on radiological information. The purpose of the present study was to define which imaging classification system could provide the best morphological and clinical-surgical correlations for cervical spine traumas.Methods: We retrospectively analyzed patients evaluated for cervical spine trauma at our Institution in the period 2015-2020. Information regarding the morphological examination (using CT and MRI), the neurological evaluation, and the therapeutic management were collected. C3-C7 fractures were classified according to the SLIC and AOSpine criteria; axial lesions were classified according to the modified AOSpine for the C1-C2 compartment and through the Roy-Camille and the Anderson D'Alonzo system for the odontoid process of the axis.Results: 29 patients were included in the final study population. Nine patients with axial spine trauma and 21 with subaxial cervical spine trauma. A conservative approach was applied in 16 patients while nine patients underwent neurosurgery. Considering the therapeutical indications provided by the SLIC system, a 76.9% accordance was found for patients with a 4 score undergoing neurosurgery. Regarding the AOSspine classification, a 28.6% concordance was observed for patients classified group B being treated with a posterior neurosurgical approach, while for patients belonging to subgroup C, considered for anterior neurosurgical approach, a 66.7% accordance was calculated.Conclusions: The study demonstrated a better morphological correlation for the AOSpine classification in subaxial trauma and the AOSpine and Anderson D'Alonzo in axial trauma. The therapeutic indication found a better correlation in the SLIC classification for subaxial trauma and the Anderson D'Alonzo for axial ones.